Effect of the Survival Judgment Task on Memory Performance in Subclinically Depressed People - Nouchi, Rui; Kawashima, Ryuta (Frontiers in Psychology, 2012)
Many reports have described that a survival judgment task that requires participants to judge words according to their relevance to a survival situation can engender better recall than that obtained in other judgment tasks such as semantic or self-judgment tasks. We investigated whether memory enhancement related to the survival judgment task is elicited or not in subclinically depressed participants. Based on the BDI Score, participants were classified as either depressed or non-depressed participants. Then 20 depressed participants and 24 non-depressed participants performed a survival judgment task and an autobiographical recall task. Results showed memory enhancement related to the survival judgment task in both depressed and non-depressed participants, but showed lower memory enhancement related to the survival judgment task in depressed participants than in non-depressed participants. These results suggest that the survival judgment task benefit is a robust phenomenon. Moreover, that benefit was reduced by depressed emotion. The combination hypothesis better explains the mechanism of memory enhancement related to the survival judgment task than the functional, emotional and arousal or congruency hypothesis does.